Model Pembelajaran Seni Musik dalam Bentuk Ansambel untuk Siswa Sekolah Menengah Pertama - R. Taryadi, Tri Wahyu Widodo, dan Bambang Riyadi (EKSPRESI, 2009)
Music Education Model in Ensemble Form for Junior High School Students. There are two music education models applied in Junior High School, namely lecturing and task assigning. These two methods are unattractive for the students. Now, there is a new model that developing, the music ensemble model. The model is considered more interes11ng and interactive. However it still weak in terms of the instruction techniques. This writing describes a model of students group work in learning music. It is assumed that the model will promote the students' creativity, and also students ' aesthetic, ethic and artistic sensitiveness so that it will support the pupils' character building and other lessons as well. Keywords: Method, technique, music ensamble.